Beyond type 2 diabetes, obesity and hypertension: an axis including sleep apnea, left ventricular hypertrophy, endothelial dysfunction, and aortic stiffness among Mexican Americans in Starr County, Texas. Issue 1 (December 2016) - Hanis, Craig; Redline, Susan; Cade, Brian; Bell, Graeme; Cox, Nancy; Below, Jennifer; Brown, Eric; Aguilar, David
Abstract Background There is an increasing appreciation for a series of less traditional risk factors that should not be ignored when considering type 2 diabetes, obesity, hypertension, and cardiovascular disease. These include aortic stiffness, cardiac structure, impaired endothelial function and obstructive sleep apnea. They are associated to varying degrees with each disease categorization and with each other. It is not clear whether they represent additional complications, concomitants or antecedents of disease. Starr County, Texas, with its predominantly Mexican American population has been shown previously to bear a disproportionate burden of the major disease categories, but little is known about the distribution of these less traditional factors. Methods Type 2 diabetes, obesity and hypertension frequencies were determined through a systematic survey of Starr County conducted from 2002 to 2006. Individuals from this examination and an enriched set with type 2 diabetes were re-examined from 2010 to 2014 including assessment of cardiac structure, sleep apnea, endothelial function and aortic stiffness. Individual and combined frequencies of these inter-related (i.e., axis) conditions were estimated and associations evaluated. Results Household screening of 5230 individuals aged 20 years and above followed by direct physical assessment of 1610 identified 23.7 % of men and 26.7 % of women with type 2 diabetes, 46.2 and 49.5 % of men and women, respectively with obesity and 32.1 and 32.4 % with hypertension. Evaluation of pulse wave velocity, left ventricular mass, endothelial function and sleep apnea identified 22.3, 12.7, 48.6 and 45.2 % of men as having "at risk" values for each condition, respectively. Corresponding numbers in women were 16.0, 17.9, 23.6 and 28.8 %. Cumulatively, 88 % of the population has one or more of these while 50 % have three or more. Conclusions The full axis of conditions is high among Mexican Americans in Starr County, Texas. Individual and joint patterns suggest a genesis well before overt disease. Whether they are all mediated by common underlying factors or whether there exist multiple mechanisms remains to be seen.